Comprehensive Care Management in Conjunction with Sputum Cytometry-Guided Pharmacotherapy in a Post-Discharge Clinic for Patients with COPD. (4th July 2021) - Ho, Terence N.; Wald, Joshua; Borhan, Sayem; Lauks, Sylvia; Campbell, Alec; Chaput, Claire; Pierce, Mary; Perkins, Janice; Camera, Julianne; MacPherson, Ana; Cox, Gerard; Raghavan, Natya; et al.
Abstract: Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) are amongst the most common reasons for hospital admission, and recurrent episodes occur frequently. Comprehensive care management (CCM) strategies have modest effect in preventing re-admissions. The objectives of this study were to examine the utility of optimizing anti-inflammatory therapy guided by sputum cytometry in the post-hospitalization setting, and to assess the feasibility and effectiveness of a clinic combining CCM and sputum-guided therapy. This is an observational study examining patients who received open-label CCM and sputum cytometry-guided pharmacotherapy in a COPD post-discharge clinic. Referral was based on high risk for readmission after hospitalization for AECOPD. The primary outcome was the change in COPD-related healthcare utilization before and after Visit 1, and this was analyzed with a mixed-effects negative binomial model controlling for age, number of follow-up clinic visits, pack years, current smoking and FEV1 . Of 138 patients referred to the clinic, 73% attended at least one visit. Mean FEV1 was 42.8 (19.3) % predicted. Of the patients attending clinic, 42.6% produced an adequate sputum sample, and 32.7% had an abnormal sputum. By individual, infectious bronchitis was the most common (25.7%), followed by eosinophilic bronchitis (13.9%). Comparing the 6-months prior to and after the first clinic visit, there was a lower incidence rate ratio after visit 1 for COPD-related healthcare utilization (0.26 (95%CI 0.22, 0.33; p  < 0.001)). A COPD post-discharge clinic combining sputum-guided treatment and CCM was feasible and associated with a nearly 75% reduction in the incidence of COPD-related healthcare utilization.